DECOLONIZING THE RESEARCH AND RESEARCH METHODOLOGY IN SOCIAL SCIENCES: PERSPECTIVES OF UNIVERSITY TEACHERS - Amna Iftikhar; Mohsin Ali; Umar Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
The aim of this qualitative study is to investigate the impact of research and research methodology on science sciences from the perspective of university teachers. Specifically, the study aimed to understand how University teachers view on decolonization Eurocentric social sciences discourse and techniques of research used in social sciences .Using a purposive sampling technique, 15 teachers from public universities were selected for in-depth interviews. Key themes and categories were extracted from the thematic analysis process. The main strategies suggested by interviewees for decolonization of social sciences in Pakistan include indigenous epistemological approaches, hybrid studies and alternative, regional studies, and indigenous knowledge and research methods. Based on the findings of this study, the perception that ignores indigenous knowledge, the value of collaborative research, grounds for learning, respect and dignity in mainstream research needs to be changed.